The Impact of Transportation on The Avocado Market in Tanzania - Tumaini, Steven; Ghahula, Raphael; Macha, Salvio (European Scientific Journal, ESJ, 2024)
Avocado (Persea americana) is grown in many nations throughout Africa, Asia, Europe, and South America. The climate of Tanzania offers a perfect habitat for growing avocados. This paper investigates how transportation affects the Tanzanian avocado industry. Data were gathered from 505 farmers and 37 categories/groups using a cross-sectional design. Data analysis was done using SPSS where descriptive statistics and the chi-square test. A one-way analysis of variance (ANOVA) with Tukey’s Honest Significant Difference (HSD) test at p < 0.05 was also done. According to the results, local avocado output is dominated by men (79% male vs. 21% female). The result of the binary logit model revealed that the participation of avocado producers in a high-value market was influenced by age, educational status, the number of avocados sold, the price of avocado, and market information. With sorting (12%), grading (7%), and packaging (9%), quality during production was judged most important (25%), followed by harvesting (16%), storage (16%), and transportation (15%) with less relevance were factors impacting quality. Improving the avocado market for growers depends on addressing these problems at the national, regional, and district levels. Hence, transportation has a big influence on the avocado industry since smallholder growers have great difficulties influencing market access and produce quality. Improvement of transport infrastructure and support systems at the national, regional, and district levels will help to boost the avocado market.